Effects of green tea on prostate carcinogenesis in rat models and a human prostate cancer xenograft model. Issue 11 (29th April 2022) - Bosland, Maarten C.; Horton, Lori; Condon, Mark S.
Abstract: Background: There is evidence to suggest that green tea soy may have protective effects against prostate cancer, but there are several epidemiologic and clinical studies that did not identify such an effect. We tested the notion of protective effects in a rat model of prostate carcinogenesis that has been predictive of the effects of selenium and vitamin E in randomized clinical trials and a human prostate cancer xenograft model in nude mice and rat prostate tumor cells transplanted in immune‐competent syngeneic animals. Methods: Prostate cancer was induced in rats with methylnitrosourea and testosterone and tumor incidence was determined. Subcutaneous tumor growth was measured resulting from injected cells isolated from rat prostate cancers grafted in syngeneic animals and from the prostate‐specific antigen (PSA)‐producing human prostate cancer PC346 xenografted in nude mice. Brewed decaffeinated green tea infusion or caffeinated green tea extract and the same 300 mg/ml concentration of caffeine were provided in drinking water of the rats and nude mice. Results: Caffeinated green tea extract and caffeine provided in drinking water did not modify the induction of prostate cancer in the rat model compared with control rats. The same drinking water treatments also did not affect the growth and PSA production of PC346 human prostate cancer xenografts in nude mice and the growth of two transplantable rat prostate cancer tumor lines in Wistar Firth rats. Brewed green tea infusion as drinking water did also not affect tumor growth in these xeno‐ and allograft models. Conclusion: These animal studies with drinking water exposure to green tea and caffeine do not support the idea that green tea is protective against prostate cancer.